Crystal structure of 2-({[5-(adamantan-2-yl)-2-sulfanylidene-1,3,4-oxadiazolidin-3-yl]methyl}amino)benzonitrile, C20H22N4OS - Al-Wahaibi, Lamya H.; Blacque, Olivier; Al-Shaalan, Nora H.; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter, 2023)
C20H22N4OS, triclinic, P1 (no. 2), a = 6.8528(3) Å, b = 11.3498(5) Å, c = 13.3896(9) Å, α = 114.083(5)°, β = 104.326(4)°, γ = 90.369(3)°, V = 914.38(9) Å3 , Z = 2, Rgt(F) = 0.0844, wRref(F2 ) = 0.2217, T = 160 K. CCDC no.: 2216322